Incidental carcinoid of appendix in cesarean section - (:unkn) unknown (My University, 2002)
A case with carcinoid tumor of the appendix was encountered incidentally during an elective cesarean section. The tumor was discovered as a result of the routine exploration of the whole abdomen. The investigation for metastasis proved no evidence of spread and the patient was treated solely by surgery.
Keywords: Adult; Female; Humans; Pregnancy; Infant, Newborn; Cesarean Section; Appendiceal Neoplasms; Appendix; Carcinoid Tumor